IMPLEMENTASI DAN PENGUJIAN KINERJA ORACLE 10g REAL APLICATION CLUSTER (RAC) PADA SISTEM OPERASI SUN SOLARIS 10 - Gatot Budi Santoso; Yanuar Indra Wirawan (Sekolah Tinggi Teknik - PLN, 2015)
During the implementation of database system, needs of getting fast, accurate and high-availabilitydata, has become major clauses for the implementation of “high-availability” system. Oracle 10gRAC is a clustered database solution that requires a two or more node hardware configurationcapable of working together under a clustered operating system. A clustered hardware solution ismanaged by cluster management software, usually provided by the hardware vendor. Theoperating system is also responsible for providing access to the shared disk subsystems. Parametersthat used for the performance testing and analyzing of Oracle 10g Real Application Cluster are thecpu idle, free memory, SGA, buffer cache, and shared pool. As result for the performance testingand analyzing, it can be concluded that Oracle 10g Real Application Cluster was really good for theimplementation of “high-availability system” concept. But it all depends to the analysis for itssystem.